Contralesional Cortical Structural Reorganization Contributes to Motor Recovery after Sub-Cortical Stroke: A Longitudinal Voxel-Based Morphometry Study - Cai, Jianxin; Ji, Qiling; Xin, Ruiqiang; Zhang, Dianping; Na, Xu; Peng, Ruchen; Li, Kuncheng (Frontiers in Human Neuroscience, 2016)
Although changes in brain gray matter after stroke have been identified in some neuroimaging studies, lesion heterogeneity and individual variability make the detection of potential neuronal reorganization difficult. This study attempted to investigate the potential structural cortical reorganization after sub-cortical stroke using a longitudinal voxel-based gray matter volume (GMV) analysis. Eleven right-handed patients with first -onset, subcortical, ischemic infarctions involving the basal ganglia regions underwent structural magnetic resonance imaging in addition to National Institutes of Health Stroke Scale and Motricity Index assessments in the acute (< 5 days) and chronic stages (1 year later). The GMVs were calculated and compared between the two stages using nonparametric permutation paired t tests. Moreover, the Spearman correlations between the GMV changes and clinical recoveries were analyzed. Compared with the acute stage, significant decreases in GMV were observed in the ipsilesional precentral gyrus (PreCG), paracentral gyrus, and contralesional cerebellar lobule VII in the chronic stage. Additionally, significant increases in GMV were found in the contralesional orbitofrontal cortex (OFC) and middle (MFG) and inferior (IFG) frontal gyri. Furthermore, severe GMV atrophy in the ipsilesional PreCG predicted poorer clinical recovery, and greater GMV increases in the contralesional OFG and MFG predicted better clinical recovery. Our findings suggest that structural reorganization of the contralesional ‘cognitive’ cortices might contribute to motor recovery after sub-cortical stroke.